THE ROLE OF OVERSIGHT IN THE IMPLEMENTATION OF CROSS-BORDER TRADE AGREEMENTS: A LITERATURE REVIEW ON THE BENEFITS FOR BORDER COMMUNITIES - Gunawan Widjaja (CV. ADIBA AISHA AMIRA, 2026)
This study discusses the role of supervision in the implementation of trade agreements between countries, with a focus on the benefits felt by communities in border areas. Through a literature review, this study analyses various sources of literature related to supervisory mechanisms, challenges in their implementation, and the positive impacts on local communities. The findings reveal that effective oversight not only prevents illegal trade practices and regulatory abuse but also enhances the economic and social well-being of border communities through fairer market access, protection of legal businesses, and improved security and empowerment of local communities. Therefore, strengthening the monitoring system through inter-agency collaboration, community participation, and the use of technology is key to the successful implementation of trade agreements that have a positive impact on the development of border areas.